(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
As the As the automobile industry develops and the population increases, the demand for it increases. Therefore, reducing the fuel problem and environmental pollution remains one of the pressing issues. All known automobile concerns and institutions specializing in ICE problems are trying to solve them by means of a turbo device to improve the ICE. This makes the design structure of the car engine complex. It is necessary to simplify the car engine for long-term high-quality operation and increased fuel efficiency. The solution to these problems can be found by increasing the compression ratio of the engine. Currently, some research is being conducted to increase the compression ratio of internal combustion engines.